Hotel General Manager’s Perception of the Factors that Affect Women Career Progression in the Hospitality Industry in Kenya - Nzioka, Alice M.; Ondigi , Alice; Khayiya , Rosemarie (African Journal of Education,Science and Technology (AJEST), 2015)
The entry of women into the professional world has, without a doubt, changed the dynamics of the workplace over the past few decades. Women bring an element of diversity in the workplace that cannot be ignored. However in most organizations there was a tendency for women to be over represented in the lower levels of an industry; but underrepresented at senior levels. When it comes to the hospitality industry and more specifically in the lodging sector in Kenya, records held by the Kenya Association of Hotel keepers and Caterers indicate that out of sixty six (66) hotel general managers for classified hotels at the coast region of Kenya only (3) 4% of women are in top management positions indicating that there are significant gender imbalances in the hospitality industry in Kenya. This is so in spite of a number of measures taken by the government through legislation and policy. This study sought to establish the socio- cultural and organizational factors that affect women career progression in the hospitality industry. The sample for this study was forty men and women general managers, forty three female hotel line managers and supervisors. The study used questionnaire and FGDs to collect data. Qualitative and quantitative data analysis was used. This study found biases in management practices in deference to official policy on gender equality. The industry lacks objective selection and promotion practices and relies on networks for executive search. From the findings of this study it was concluded that although individually the perception of the hotel general managers was influenced by their socio-economic and demographic factors their perception seemed to reflect the hospitality industry organizational culture and as such determine if the hospitality career was regarded as inclusive or exclusive of female employees.